2018
DOI: 10.1111/sltb.12500
|View full text |Cite
|
Sign up to set email alerts
|

The Capability for Suicide in Firefighters

Abstract: CSE-T within the context of significant other support is important to consider in understanding firefighter mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…As expected, the results of this study showed a weak positive correlation between perceived social support and suicidal ideation. These findings are consistent with previous studies in firefighters that have suggested that these variables may be related Streeb, Shoji, & Benight, 2019). Perceived social support also showed a significant independent relationship with suicidal ideation (p<0.001) with perceived social support accounting for 4.7% of the variance in suicidal ideation in this sample.…”
Section: Discussionsupporting
confidence: 92%
“…As expected, the results of this study showed a weak positive correlation between perceived social support and suicidal ideation. These findings are consistent with previous studies in firefighters that have suggested that these variables may be related Streeb, Shoji, & Benight, 2019). Perceived social support also showed a significant independent relationship with suicidal ideation (p<0.001) with perceived social support accounting for 4.7% of the variance in suicidal ideation in this sample.…”
Section: Discussionsupporting
confidence: 92%
“…Scores can range from 20 to 140, with higher scores indicating a higher perceived ability to cope with work-related stressors and demands. A study by Streeb et al (2019) successfully used this instrument to measure firefighters' ability to cope with potential occupational stressors. The FFCSES has demonstrated good internal consistency (Cronbach's αs = .90-.92; Lambert et al, 2012).…”
Section: Ffcsementioning
confidence: 99%
“…CSE-T refers to one's perceived ability to self-manage the stressors and recovery demands related to trauma exposure (Benight & Bandura, 2004;Benight et al, 2015). In support of this construct, Streeb et al (2019) found that CSE-T meditated the association between critical incidents and factors related to suicide risk among firefighters. FFCSE, another potential protective factor of interest, refers to a firefighter's perceived ability to manage occupational exposures and demands (Lambert et al, 2012).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…It is often committed because of disappointment, explained by mental problems, depression, bipolar disorder, schizophrenia, love failure, alcohol addiction, and drug use. One American dies from suicide every 12.8 min, making suicide the tenth leading cause of death in the United States according to the American Foundation for Suicide Prevention ( 6 ). In most cases, stress factors such as financial problems or interpersonal problems play a significant role in suicide.…”
Section: Introductionmentioning
confidence: 99%